Dampak Perubahan Perilaku Konsumen terhadap Kelangsungan Usaha Ritel Tradisional: Studi Kasus Pasar Sentral Pemangkat Kalimantan Barat - Rudi Hartono (Jurnal Ilmu Pendidikan dan Sosial, 2025)
The rapid development of technology and internet penetration over the past five years has significantly transformed consumer purchasing behavior, shifting a substantial portion of transactions to e-commerce platforms. This shift has had a profound impact on traditional markets, including Pasar Sentral Pemangkat, which was once bustling with trade in clothing, groceries, sandals, and shoes. This study aims to analyze the impact of changing consumer behavior on the sustainability of traditional retail businesses and to explore the factors contributing to the market’s decline. A qualitative case study approach was employed, utilizing in-depth interviews with traders, market managers, and consumers. The findings reveal that the transition to online shopping, more competitive pricing, and shopping convenience are the primary factors influencing the sustainability of retail businesses in Pasar Sentral Pemangkat. These findings highlight the urgent need for traditional markets to adopt digital transformation strategies, improve market accessibility, and implement competitive pricing mechanisms to remain relevant in the evolving retail landscape.